Understanding gas pricing mechanisms: Implications for the Asian market - Yifei Cai; Yanrui Wu (Asian Development Bank Institute (ADBI), 2020)
This paper aims to understand the gas-pricing mechanism in the major markets and hence draw implications for gas-pricing reform in Asia. It adopts the bootstrap sub-sample rolling-window Granger test to investigate the causality between crude oil and natural gas prices. Unlike the estimations based on full-sample data with the problem of parameter constancy, the rolling-window technique can provide evidence with time-varying properties. The findings in this paper support a coupling relationship between oil and gas prices in Japan before 2013 and a mixed relationship after that. In Europe, the relationship is mixed. Lastly, the study identifies a decoupling relationship in the US. The oil supply and demand, OPEC decisions, and the financial crisis are likely to affect the traditional oil indexation. However, the shale gas revolution tends to affect the deviation between crude oil and gas price changes in the US. The empirical results suggest the necessity to establish trading hubs in Asia and Europe so that gas pricing can fully reflect the fundamentals in gas markets and help to achieve more efficient gas allocation.
Keywords: Q31; Q41; 330; natural gas pricing; oil indexation; time-varying Granger causality test; rolling-window technique; Asia